Changes in salivary and plasma cortisol levels in Purebred Arabian horses during race training session. (21st November 2013) - Kędzierski, Witold; Cywińska, Anna; Strzelec, Katarzyna; Kowalik, Sylwester
Abstract Physical activity and stress both cause an increase in cortisol release ratio. The aim of this study was to evaluate the use of saliva samples for the determination of cortisol concentrations indicating the work‐load level in horses during race training. Twelve Purebred Arabian horses aged 3–5 years were studied during the routine training session. After the warm‐up, the horses galloped on the 800 m sand track at a speed of 12.8 m/s. Three saliva samples, and three blood samples were collected from each horse. Both types of samples were taken at rest, immediately after return from the track and after 30 min restitution. The concentrations of blood lactic acid (LA), and cortisol in saliva and plasma samples were measured and analyzed. Blood LA, plasma and salivary cortisol levels increased significantly after exercise (P < 0.05). Salivary cortisol concentration determined 30 min after the exercise correlated significantly with plasma cortisol level obtained immediately after exercise (P < 0.05) as well as measured 30 min after the end of exercise (P < 0.05). The determination of cortisol concentration in saliva samples taken from racehorses 30 min after the end of exercise can be recommended to use in field conditions to estimate the work‐load in racehorses.